Health Literacy and Demographic Disparities in HIV Care Continuum Outcomes - Rebeiro, Peter F. (AIDS Behav, 2018)
Studies evaluating the association between human immunodeficiency virus (HIV) infection continuum of care outcomes [antiretroviral (ART) adherence, retention in care, viral suppression] and health literacy have yielded conflicting results. Moreover, studies from the southern United States, a region of the country disproportionately affected by the HIV epidemic and low health literacy, are lacking. We conducted an observational cohort study among 575 people living with HIV (PLWH) at the Vanderbilt Comprehensive Care Clinic (Nashville, Tennessee). Health literacy was measured using the brief health literacy screen, a short tool which can be administered verbally by trained clinical personnel. Low health literacy was associated with a lack of viral suppression, but not with poor ART adherence or poor retention. Age and racial disparities in continuum of care outcomes persisted after accounting for health literacy, suggesting that factors in addition to health literacy must be addressed in order to improve outcomes for PLWH.